1969
DOI: 10.1530/acta.0.0620021
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Antithyroid Activity of Naturally Occurring L-5-Vinyl-2-Thiooxazolidone and Its Urinary Metabolite in Rats

Abstract: Rats were force fed a single dose of 20, 40, 80, 160, 320, 640, 1280 and 2560 μg L-5-vinyl-2-thiooxazolidone (VTO) and injected with 131I one hour later. The 131I uptake, biosynthesis of thyroid hormones and PB131I were measured 4 h after the administration of 131I. Under these conditions, a higher antithyroidal effect with VTO was found in rats fed a normal diet (ND) for 10 days before the experiment as compared with rats fed a low iodinediet (LID) for the same period. The results are described in detail. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…From the previous data of Langer et al, 23 who reported that 77 lmol of goitrin did not decrease thyroidal radioiodine uptake, 23 it is reasonable to infer that a single serving of brassica vegetables with less than 70 lmol of progoitrin would be unlikely to result in decreased thyroid hormone production in humans. Specifically, ingestion of commercial broccoli and broccoli rabe, which each contain less than 10 lmol progoitrin per 100-g serving, would appear to pose minimal risk of thyroidal toxicity.…”
Section: Progoitrin Concentrations That Results In Decreased Thyroid Hmentioning
confidence: 88%
See 2 more Smart Citations
“…From the previous data of Langer et al, 23 who reported that 77 lmol of goitrin did not decrease thyroidal radioiodine uptake, 23 it is reasonable to infer that a single serving of brassica vegetables with less than 70 lmol of progoitrin would be unlikely to result in decreased thyroid hormone production in humans. Specifically, ingestion of commercial broccoli and broccoli rabe, which each contain less than 10 lmol progoitrin per 100-g serving, would appear to pose minimal risk of thyroidal toxicity.…”
Section: Progoitrin Concentrations That Results In Decreased Thyroid Hmentioning
confidence: 88%
“…One study assessed the change in radioactive iodine uptake by the thyroid glands of human subjects following the administration of recrystallized goitrin. 23 The authors reported that 25 mg (194 lmol) was the minimal amount of goitrin required to decrease the uptake of radioiodine; in contrast, a smaller ingested amount, 10 mg (70 lmol), caused no inhibition of uptake.…”
Section: Non Enzymaɵcmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensity of these effects varies with the animal species and, of course, the amount of GSL in their food (Bourdon et al 1981 ;Butler et al 1982;Bell, 1984;Etienne & Dourmad, 1987). In humans, reduced iodine uptake by the thyroid gland was reported after daily ingestion of 500 g cabbage for 2 weeks (Langer et al 1971) or after a single meal of 300 to 500 g swede or turnip (Greer & Astwood, 1948). However, a more recent study by McMillan et al (1986) did not lead to hypothyroidism in human volunteers consuming 150 g Brussels sprouts daily for 4 weeks.…”
Section: Toxicity Of Glucosinolates a N D Glucosinolate Derivativesmentioning
confidence: 97%
“…Goitrin (5-vinyloxazolidine-2-thione), one of the major derivatives of progoitrin, has been the most extensively studied GSL derivative, as far as toxicity is concerned. This goitrogen, very potent even at low doses (Krusius & Peltola, 1966;Langer & Michajlovskij, 1969;Akiba & Matsumoto, 1976), can induce decreased uptake of iodine by the thyroid gland in humans (Astwood et al 1949) and in rats, modify the triiodothyronine : thyroxine ratio and alter the histological pattern of the thyroid in rats (Lo &Hill, 1971 ;Bell et al 1972;Lo & Bell, 1972). It seems that goitrin interferes with organic iodination of thyroxine precursors in the gland, thus leading to compensatory goitre (Akiba & Matsumoto, 1976;Elfving, 1980).…”
Section: Toxicity Of Glucosinolates a N D Glucosinolate Derivativesmentioning
confidence: 99%